2021
DOI: 10.1177/08862605211001472
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Contexts of Intimate Partner Violence Among Young, Partnered Gay, Bisexual and Other Men Who Have Sex With Men in the United States

Abstract: There has been a growth in research illustrating that gay, bisexual, and other men who have sex with men (GBMSM) experience intimate partner violence (IPV) at rates that are comparable to those among heterosexual women. However, the majority of research on IPV among same-sex male couples has focused on adults, and research on the experience of IPV among younger men (those aged under 18), remains at a nascent stage, despite knowledge that IPV is often common among younger men. This article adds to the growing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 48 publications
0
20
0
1
Order By: Relevance
“…It is plausible that experiences and forms of IPV may be underreported, which necessitates future research to better understand and explicitly address experiences of IPV among YSMM. In particular, Stephenson et al (2021) found that YSMM often struggled with defining sexual IPV, and thus participants may be misreporting or underreporting IPV based on their definitions of what constitutes sexual violence. Participants were recruited online using convenience sampling methods, which has important implications for generalizability.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that experiences and forms of IPV may be underreported, which necessitates future research to better understand and explicitly address experiences of IPV among YSMM. In particular, Stephenson et al (2021) found that YSMM often struggled with defining sexual IPV, and thus participants may be misreporting or underreporting IPV based on their definitions of what constitutes sexual violence. Participants were recruited online using convenience sampling methods, which has important implications for generalizability.…”
Section: Limitationsmentioning
confidence: 99%
“…Tornello et al (2014) found that young sexual minority women were 3 to 6 times more likely than heterosexual female youth to experience sexual IPV in their relationships and there is emerging evidence that these disparities may also exist for sexual minority men (Kann et al, 2016;Walters et al, 2013). In a qualitative study with young, partnered sexual minority men from ages 15 to 19 years, Stephenson et al (2021) found that experiences of sexual IPV were described along with struggles around talking about sexual consent and establishing consent with sexual partners. Participants discussed feeling "uncomfortable" with their own or their partners' lack of verbal consent during sex and feeling coerced into unwanted sex.…”
Section: Introductionmentioning
confidence: 99%
“…Intimate partner violence (IPV) is a serious public health concern affecting sexual minorities to the same extent as heterosexual people, if not even more [ 1 , 2 , 3 ]. Only in the past few decades researchers turned their attention to same-sex intimate partner violence (SSIPV; [ 4 ]). Nevertheless, IPV among same-sex couples remains poorly discussed on a public level and bias in media representations have been documented, which contribute to the poor understanding of the phenomena [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also identified several correlates of DV victimization during the COVID-19 lockdown, including increased stress or anxiety level, increased alcohol use, housing instability due to COVID-19, and recent depressive symptoms. Stringent stay-at-home orders may have led to a syndemic of worsened mental health, increased substance use, and DV victimization ((Stephenson et al, 2021)). It is also concerning that participants experiencing DV victimization were more than twice as likely to become homeless or have to stay with friends or relatives during the pandemic than those without experiencing DV victimization.…”
Section: Discussionmentioning
confidence: 99%